Evaluate the suitability of regional spatial planning Tanggamus Regency - Fasa, Achmad Saeful (Trigin Publisher, 2024)
Organizing spatial planning is important to achieve safe, comfortable and sustainable spatial conditions. Regional Government plays a key role in preparing regional spatial plans and controlling space utilization. Monitoring and evaluation is carried out routinely to assess the suitability of space utilization. Evaluation of the Suitability of the Spatial Planning of Tanggamus Regency in 2023 show a level of conformity of 88.71%, in the QUALITY category. The conclusion of the analysis highlights aspects that need to be considered in space management in Tanggamus Regency, providing a basis for policy formulation that maintains consistency in space use and increases conformity with spatial plans.